Early investigational drugs for hearing loss. (February 2015) - Mukherjea, Debashree; Ghosh, Sumana; Bhatta, Puspanjali; Sheth, Sandeep; Tupal, Srinivasan; Borse, Vikrant; Brozoski, Thomas; Sheehan, Kelly E; Rybak, Leonard P; Ramkumar, Vickram
<x xml:space="preserve">Abstract</x> Introduction: Sensorineural hearing loss (HL) is becoming a global phenomenon at an alarming rate. Nearly 600 million people have been estimated to have significant HL in at least one ear. There are several different causes of sensorineural HL included in this review of new investigational drugs for HL. They are noise-induced, drug-induced, sudden sensorineural HL, presbycusis and HL due to cytomegalovirus infections. Areas covered: This review presents trends in research for new investigational drugs encompassing a variety of causes of HL. The studies presented here are the latest developments either in the research laboratories or in preclinical, Phase 0, Phase I or Phase II clinical trials for drugs targeting HL. Expert opinion: While it is important that prophylactic measures are developed, it is extremely crucial that rescue strategies for unexpected or unavoidable cochlear insult be established. To achieve this goal for the development of drugs for HL, innovative strategies and extensive testing are required for progress from the bench to bedside. However, although a great deal of research needs to be done to achieve the ultimate goal of protecting the ear against acquired sensorineural HL, we are likely to see exciting breakthroughs in the near future.